Marine Biodiversity - Marine Biodiversity (Springer Nature, 2026)
Marine Biodiversity is a peer-reviewed international journal devoted to all aspects of biodiversity research in marine ecosystems and in particular, encourages contributions dealing with the understanding of the evolution and maintenance of biodiversity in marine systems and the role of species in structuring marine ecosystem functioning.
FI 0.5
Q3
Keywords: Earth; Space & Environmental Sciences; Oceanography & Paleoceanography; Acuerdos transformativos; Transformative agreements; Biodiversidad marina; Ecosistemas marinos; Diversidad de especies; Ecología marina